Responsibilities Of Notaris On Making Authority To Sell Deed Which Contain Power Clause (Case Study Of Decision Number 016 / G / 2014 / Ptun.Semarang) - Diyah Ayu Fatkhurochmah; Dedy Nurjatmiko; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The granting of power in Indonesian positive law is set forth in Book III Chapter XVI starting from Article 1792 to 1819 of the Civil Code. Giving power to sell is one form of power of attorney that is often found in the community. Article 1813 of the Civil Code on the expiry of the power of attorney may be disregarded, and this is what the power-granting institution is called the Absolute Power. The Absolute Authority is stipulated in the Instruction of the Minister of Home Affairs number 14 year 1982 concerning the prohibition of the use of absolute power clause in the deed of sale and the deed of sale and purchase binding. The legal method used was the normative juridical method, with the specification of descriptive analysis. The data analysis used was qualitative analysis. Based on the results of research and discussion, it can be concluded that the legal protection for the authorizer in the production of the power of sale deed may be granted if the power of sale deed is made in an authentic deed—it is the perfect evidence. Article 1800 to 1806 of the Civil Code that governs the duty of the assignee is a form of legal protection granted by law to the authorizer. The verification and judgment process by the judge to decide the case number 016/G/2014/PTUN.Smg was done equally between the plaintiff and the defendant and given the same right to prove, and the judge in accordance with the principle of the State Administrative Judge is active, of irrelevant evidence, no longer considered, but constituted a unity in the decision of this dispute.Keywords: Power of Attorney; Power of Sale; Absolute